Candice Lin: Landscape, Territory and Boundaries - Baltodano Román, Gabriel (2017)
An analysis is provided of the ideological contents of the watercolor “Birth of a Nation” (2008), by Candice Lin. This interpretation of this pictorial landscape is based on notions such as territory, cannibal tropes, tropical botanical types and border thinking. The artist activist reflects here on the regime of visual representation. Using different formal procedures, Lin questions central precepts of the colonialist mentality, in contrast with indigenous conceptions.